2007
DOI: 10.1103/physreve.75.056105
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for fragment formation in brittle solids

Abstract: A model for mode I fracture in brittle materials is used to elucidate the relationship between characteristics of the fracture process, such as crack roughness, fractal dimension, and fragment size distributions. It is shown that different roughness in local regions of the crack path leads to different mechanisms for the subsequent fracture of those regions. Formation of two robust power laws for the distribution of formed fragments is observed, governing the size distribution of smaller and larger fragments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…DEM simulations of fragmentation processes have been able to reproduce the power law functional form [2][3][4][5][6]15] with various types of cohesive interactions from LennardJones solids [14,[31][32][33] through spring lattices [30,33] to beam networks [4,8,15]. The concept of universality motivated the development of stochastic models of fragmentation [34,35], among which the crack branching-merging scenario proved to be very successful [36,37]. Recent DEM simulations of a generic model of brittle solids have reported a surprising result: The fragment mass exponent τ of a two-dimensional disk impacted against a hard wall was found to slowly increase with the imparted energy E 0 .…”
Section: Fragment Mass Distributionmentioning
confidence: 99%
“…DEM simulations of fragmentation processes have been able to reproduce the power law functional form [2][3][4][5][6]15] with various types of cohesive interactions from LennardJones solids [14,[31][32][33] through spring lattices [30,33] to beam networks [4,8,15]. The concept of universality motivated the development of stochastic models of fragmentation [34,35], among which the crack branching-merging scenario proved to be very successful [36,37]. Recent DEM simulations of a generic model of brittle solids have reported a surprising result: The fragment mass exponent τ of a two-dimensional disk impacted against a hard wall was found to slowly increase with the imparted energy E 0 .…”
Section: Fragment Mass Distributionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] This corresponds to a regime in which the fragment distribution has certain aspects of scale-invariance and can be treated as a fractal with a particular dimensionality. Oddershede and coworkers suggested that the power-law behavior observed in brittle fragment distributions could be interpreted in the context of self-organized criticality, and proposed a fragment distribution of the form,…”
Section: Introductionmentioning
confidence: 99%
“…2 we present a small collection of crack patterns obtained by a point-like impact. Understanding such fracture or fragmentation patterns and modelling them is a challenge for modern computational material science and physics [4][5][6][7][8][9][10]. Fracture and elasticity of soda-lime glass has been studied and modelled for a long time [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%